How should the ophthalmologists treat the methanol-induced toxic optic neuropathy? - Sanaei-Zadeh, H (Nepalese Journal of Ophthalmology, 2012)
No abstract available.DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6563 Nepal J Ophthalmol 2012; 4 (2): 348-350